Jezik in etnična pripadnost v Porabju - Nećak Lük, Albina (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 1994)
The analysis of data, collected in Monošter within the research project "Interethnic relations in the Slovene ethnic territory" showed a group of respondents that declared themselves as Hungarians though there are several elements pointing at their Slovene origin and a certain degree of attachment to the Slovene ethnic heritage. The present article is primarily focussed uponthe behaviour of this group as compared with other respondents (Slovenes and Hungarians), who, regarding the declaring of their ethnic origin, do not deviate from the original community. The article therefore highlights the sociolinguistic situation in Porabje along with the related aspects of linguistic knowledge and communicative activity of our respondents.
Keywords: jezikovne manjšine; Madžarska; narodne manjšine; Porabje; porabski Slovenci